2020
DOI: 10.1186/s40486-020-00123-y
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Bénard instability in nanofluids: a comprehensive review

Abstract: The extraordinary enhancement in heat transfer efficiency of nanofluids at extremely low volume fractions has attracted a lot of attention in identifying the governing mechanisms. The nanoscale effects, Brownian motion (random motion of particles inside the base fluid) and thermophoresis (diffusion of particles due to temperature gradient) are found to be important slip mechanisms in nanofluids. Based on these findings, a set of partial differential equations for conservation laws for nanofluids was formed. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 102 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…Only the recent work 37 had performed a preliminary observation for the formation of Bénard cell in a nanofluid layer with a free surface. As the review report 38 suggested, further experimental investigations are necessary to verify the results of theoretical works and this subject needs more interdisciplinary research in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the recent work 37 had performed a preliminary observation for the formation of Bénard cell in a nanofluid layer with a free surface. As the review report 38 suggested, further experimental investigations are necessary to verify the results of theoretical works and this subject needs more interdisciplinary research in the future.…”
Section: Resultsmentioning
confidence: 99%
“…They also derived an analytic expression for the thermal Rayleigh number with free–free boundary conditions to validate the experimental results. A comprehensive review of Rayleigh–Bénard instability in nanofluids was presented by Ahuja and Sharma 38 in which a large number of theoretical studies pertaining to the instability of a horizontal nanofluid layer were introduced. The presence of nanoparticles was found to hasten the onset of instability generally in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Equation ( 20) is then substituted into equation ( 19) to give , (21) and the general solution of can be derived by integrating Eq. ( 20) to give…”
Section: Basic State Solutionmentioning
confidence: 99%
“…17 Recently, a comprehensive review has been proposed to summarize all the studies related to the Rayleigh-Bénard instability problems in nanofluids for both porous and non-porous media. 21 Although the study 13 has provided an initiatory exploration for the thermal instability characteristics of nanofluid in a horizontal porous medium layer, a potential contradiction exists when thermophoresis effect is pronounced. As elucidated in the recent works, 18,22 the thermophoretic diffusion coefficient is actually dependent upon the nanoparticle volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of nanofluids as the medium of heat transfer is greatly reliant on Rayleigh numbers of base fluid as well as nanofluid. The number points to the relative magnitude of viscous and buoyancy forces in the fluid 29,30 which are given by Equations (1) and (2) respectively. Viscous force=ϑd3kρCp. Buoyancy force=gβΔT.…”
Section: Impact Of Rayleigh–bénard Convection On Heat Transfer Effect...mentioning
confidence: 99%